Facilitating Communication with Diverse Teams - MaryJane Lewitt (Academic Chairpersons Conference Proceedings, 2020)
Non- hierarchical communication structures are associated with greater clarity across all levels. These structures can be implemented in a variety of ways under different circumstances. A variety of communication processes should be implemented to improve communication with individualizing the technique to the type of information being communicated.
Keywords: communication; teamwork; collaboration; teams; leadership